심부표층각막이식술에서 전층각막이식술로 전환한 환자에서 발생한 이중데스메막 1예 - 임종찬, 김홍균, 이준훈Jong Chan Im MD Hong Kyun Kim MD PhD Jun Hun Lee MD (Daihan angwa haghoi jabji, 2014)
목적: 심부표층각막이식술 중 데스메막이 파열되어 전층각막이식술로 전환한 환자에서 발생한 이중데스메막의 증례를 보고하고자 한다. 증례요약: 원추각막으로 진단받은 24세 여자 환자로 심부표층각막이식술을 시행하여 원추각막을 치료하고자 하였다. Big bubbletechnique를 이용하여 각막 기질과 데스메막을 분리하던 중 데스메막이 파열되어 수술 방법을 전층각막이식술로 전환하였다. 각막봉합을 마친 후 전방 내에서 데스메막이 관찰되어 공여각막의 데스메막이 박리된 것으로 생각하고 공기주입술을 시행하여 유착시켰다. 술 후 5일째 데스메막의 박리가 다시 관찰되어 2차 공기주입술을 시행하였다. 이후 이식 각막의 부종은 호전되었으나 데스메막의박리는 지속되었으며, 전안부 빛간섭단층촬영을 통하여 박리된 데스메막은 공여각막의 것이 아니라 수여각막에서 기원한 것임을 확인할 수 있었다. 시축을 가리던 이중데스메막은 수술을 통해 성공적으로 제거하였다. 환자의 각막은 투명한 상태를 유지하였고, 최대교정시력은 20/25로 측정되었다. 결론: 심부표층각막이식술에서 전층각막이식술로 전환시에 남아있는 데스메막의 제거에 주의를 기울여야 한다. 각막이식술 후의 남아있는 데스메막은 공여각막에서 유래된 것으로 오인될 수 있으며 이를 유착시키기 위해 공기주입술을 시행하는 것은 공여각막의 내피세포 손상을 유발할 수 있다. 세극등현미경 검사로 각막의 해부학적 구조를 파악하기 힘든 경우에는 전안부 빛간섭단층촬영이 많은도움이 된다. Purpose: To report a case of double Descemet’s membrane in a patient who had penetrating keratoplasty after rupture ofDescemet’s membrane during deep anterior lamellar keratoplasty (DALK). Case summary: A 24-year-old female had keratoconus in her right eye and underwent DALK for treatment. Descemet’smembrane was ruptured while separating the corneal stroma from Descemet’s membrane with the big bubble technique. The operation method was changed from DALK to penetrating keratoplasty. Detached Descemet’s membrane was observedin the anterior chamber after suturing. Sterile air was injected into the anterior chamber to attach the Descemet’smembrane. Five days after the surgery, Descemet’s membrane was detached and a second air injection was performed. Corneal edema was improved but Descemet’s membrane was re-detached. Double Descemet’s membrane was observedby anterior segment optical coherence tomography (OCT). The detached Descemet’s membrane originated from the recipient’scornea and not from the donor’s cornea. Detached Descemet’s membrane was removed successfully. Patient’scornea was clear and best corrected visual acuity was 20/25. Conclusions: When penetrating keratoplasty is performed instead of DALK, the surgeon should completely remove theremnant corneal stroma and Descemet’s membrane. Remnant Descemet’s membrane can be disregarded as it comesfrom the donor cornea. Unnecessary anterior chamber air injection causes endothelial damage. Anterior segment OCT isa useful tool to identify anatomical structures of transplanted cornea. KCI Citation Count: 0